Analysis of the Work Environment and Work Stress on Employee Performance at PT. Putikayo International Bogor - Marendra, I Gede; Fajri, Chotamul; Permatasari, Retno Japanis (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This research aims to determine the influence of the work environment and work stress on employee performance at PT. Putikayo. Based on the results obtained, the work environment does not have a significant effect on employee performance with the linear regression equation Y= 28,175+0.660 The linear regression equation value Y=22.465+0.560X2, with a value of Tcount > Ttable (5.711 > 1.677) and a significance value of 0.000. Simultaneously the work environment variables and work stress influence employee performance with a linear regression equation value of Y= 18.749 + 0.101X1 + 0.561X2, with the f test results Fcount > Ftable (17.371 > 4.047) and a significance value of 0.000.